A novel donor-π-acceptor anthracene monomer: Towards faster and milder reversible dimerization. Issue 7 (15th February 2019) - Van Damme, Jonas; van den Berg, Otto; Brancart, Joost; Van Assche, Guy; Du Prez, Filip
Abstract: A novel functional 2, 6-substituted donor-acceptor anthracene derivative, bearing a long alkyl spacer and a polymerizable end-group, is synthesized from readily available compounds. This monomer possesses conjugated electron donor and acceptor moieties to achieve UV absorption and anthracene dimerization at higher wavelengths and under milder conditions, than anthracene and other reported anthracene derivatives. The compound was shown to absorb at higher wavelengths and dimerize much faster compared to most 9-substituted anthracenes. The fast photochemical and relatively slow thermal scission of the dimers were studied and related to the chemical structure, i.e. the 2, 6-substitution. Graphical abstract: